Aplicación de los Trabalenguas, Rima y Poesía como recursos didácticos para mejorar la pronunciación fonética como habilidad de la expresión oral de los niños y niñas de 5 años de la. I. E nº 231 del sector Atahualpa del distrito de Rioja. - Peche Gonzales, Diana Edith (2008)
Having in it counts that the language in infantile education is essentially oral, therefore, and because it is in that necessity of expression it is that they should also be planned and to implement the necessary strategies for its didactic conduction that you/they put in emphasis the inherent capacities; that is to say that they promote the learning of the speaks speaking. In the 1 process of the 1 develop of the correct pronunciation the children they face many difficulties then for the diversity of sound codes that should use for what their level of organic and psychological development is not matched rhythmically, deserves the application of corrective policies in the plane of the elements phonetic of the expression. In that sense it is that our investigation was addressed toward the 1 study of the fluency in the communication, for that which we fix the purposes in the potentiation of the abilities for the pronunciation of words and sentences in the children. The strategy to apply included articulately to the tongue twister, to the it rhymes and to the poetry like main didactic resources for the training and the establishment gives of the pronunciation of the children when speaking for its characteristics special of to subject to the stimulation intensive of the pronunciation. To the long of 15 sessions it was applied a combined of tongue twister poetries and rhymes. Beginning with the uses of the tongue twister for their property of to untangle and to align the diction of the syllables words to the moment of to pronounce them. As the experiment it was applied when the school activities was already advanced, it was opted by the 1 only design later of a single group considering an alone mensuration to the term of the experimental application. To pick up the data the ready of comparison, instrument it was applied that embraced the fundamental dimensions in the fact that the difficulties of pronunciation they are manifested, among them: the omission, the substitution, the addition and the distortion each one with their corresponding indicators relating the expression of syllables and words mainly. In the analysis of the dimension for omission finds that the difficulties for the pronunciation fonémica of requires a bigger effort of to overcome them. However in what corresponds the difficulties for substitution and for insert they were overcome bigger easiness. On line general the presented favorable tendencies as to validate the applied experimental process, so that without fear to fall in the exaggeration can determine the utility and the high effectiveness of the strategy that the tongue twister, the combined it rhymes and the poetry for the correction, the accommodation and the establishment of the abilities of the children and girls for the pronunciation in the exercise of the oral expression, even at one time relatively short of pedagogic intervention technician. Based on the positive arguments exist as to confirm our central hypothesis and to notice of the achieve of the objectives proposed as main contributions scientists gotten to favor of the effective didactic handling in the marry of to face similar difficulties in the learning of the oral expression,